2008
DOI: 10.1094/cchem-85-1-0031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GABA Tea on Quality Characteristics of Chiffon Cake

Abstract: The effects of gamma aminobutyric acid (GABA) tea on the quality characteristics of chiffon cakes were studied. The viscosity and specific gravity in cake batter, and total dietary fiber, GABA, catechin, epicatechin, gallocatechin, epigallocatechin, epicatechin gallate, and epigallocatechin gallate contents, hardness, and crumb a value of baked cakes increased with increasing GABA tea level; whereas, the pH and moisture in cake batter, and the moisture, water activity, cake volume, crust L, a, b and crumb L, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 25 publications
5
24
0
1
Order By: Relevance
“…The addition of DF increased significantly (P< 0.05) the apparent viscosity values. Similar results were found from other researchers; Masoodi et al (2002) and Lee and Lin (2008) reported that apple pomace and GABA tea powder increased batter viscosity with increasing addition level as well as with decreasing particle size. Furthermore, Brockmole and Zabik (1976) attributed the higher viscosity of fiber-incorporated batters to water absorption by fiber.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The addition of DF increased significantly (P< 0.05) the apparent viscosity values. Similar results were found from other researchers; Masoodi et al (2002) and Lee and Lin (2008) reported that apple pomace and GABA tea powder increased batter viscosity with increasing addition level as well as with decreasing particle size. Furthermore, Brockmole and Zabik (1976) attributed the higher viscosity of fiber-incorporated batters to water absorption by fiber.…”
Section: Resultssupporting
confidence: 91%
“…Dietary fiber (DF) is the edible part of plants or analogous carbohydrates; it consists of polysaccharides that are resistant to digestion and absorption in the human small intestine with complete or partial fermentation in the large intestine (Lee and Lin 2008). Dietary fiber can be categorized into insoluble dietary fiber (IDF; cellulose, hemicellulose, amyloids, lignin, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, it was reported that moisture content of chiffon cake decrease with higher addition of gamma aminobutyric acid (GABA) tea powder due to lower water holding capacity of GABA tea powder compared to cake flour [22]. As concentration of YCE increases and wheat flour decreases, moisture contents notably reduced since wheat flour containing slightly more moisture content (9.00%) than YCE (5.73%).…”
Section: Resultsmentioning
confidence: 99%
“…This may be related to different water holding capacity of the YCE and flour. In a previous study, it was reported that moisture content of chiffon cake decreased with higher addition of gamma aminobutyric acid (GABA) tea powder due to lower water holding capacity of GABA tea powder compared to cake flour [8]. In the present study, even though protein content of cake added with YCE increase in line (13.3 to 15.7%) with the levels of YCE (10 to 30%), but there was no significant different compared to control.…”
Section: Nutritional Composition 0f Chiffon Cakementioning
confidence: 99%